2012
DOI: 10.1007/s00542-011-1421-9
|View full text |Cite
|
Sign up to set email alerts
|

Gold-based thin multilayers for ohmic contacts in RF-MEMS switches

Abstract: In RF-MEMS switches many reliability issues are related to the metal contacts in the switching area. The quality of this contact strongly influences switching failures due to wear, adhesion and stiction. Gold is widely used as contact material, but is a soft metal. Contact hardness can be improved preserving good conductivity and chemical inertness alternating gold layers with thin layers of other metals. A detailed study of mechanical, electrical and morphological properties of gold-chromium, gold-platinum an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Figure 2 shows that the background subtracted Raman spectra vary with CVD growth time on both experimental configurations. The spectra are normalized to the sp 3 diamond peak (1333 cm -1 ). The slight of shift from the stress-free 1332 cm -1 phonon position can be attributed to the residual stress present in the films [25].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 2 shows that the background subtracted Raman spectra vary with CVD growth time on both experimental configurations. The spectra are normalized to the sp 3 diamond peak (1333 cm -1 ). The slight of shift from the stress-free 1332 cm -1 phonon position can be attributed to the residual stress present in the films [25].…”
Section: Resultsmentioning
confidence: 99%
“…It is known that Cr tends to diffuse and react with the substrate during processing, depending upon the choice of substrate and other combined materials. For example, in NEMS/MEMS [2,3] or CMOS structures [4], the behavior of the Cr interlayers during the processing steps is of fundamental importance [5][6][7]. Recently, it was shown that thermionic emission properties can be improved by employing chromium silicide (Cr 5 Si 3 ) as an electrical nanocontact material, as it facilitates charge transfer through the Si/Au interface by lowering the Schottky barrier [8].…”
Section: Introductionmentioning
confidence: 99%
“…These reliability issues are closely related to the contact area between metals, especially in ohmic RF MEMS switches. Stiction usually originates from cold welding or hot welding [115]. Cold welding is primarily caused by atomic adhesive forces between contact materials, while hot welding is particularly crucial for switches, as it depends on the current passing through the contact point.…”
Section: Improvement Of Contact Materials and Structuresmentioning
confidence: 99%
“…From this perspective, the best approach is to increase the hardness of the gold contact points without introducing other metals on the outer surface. Mulloni et al [115,116] demonstrated that stacking platinum layers between gold not only increased the hardness of the contact points but also improved the contact surface performance. This improved gold-platinum multi-layer contact material significantly outperforms pure gold in terms of stability and shows lower serial resistance.…”
Section: Improvement Of Contact Materials and Structuresmentioning
confidence: 99%